2019
DOI: 10.1080/20008198.2019.1601989
|View full text |Cite
|
Sign up to set email alerts
|

Danger- and non-danger-based stressors and their relations to posttraumatic deprecation or growth in Norwegian veterans deployed to Afghanistan

Abstract: Objective: This study aimed to explore how exposure to danger-based and non-dangerbased stressors may influence personal changes in veterans (N = 4053) after deployment to Afghanistan. Method: Twelve war zone related traumatic events were used to form two stressor categories. The non-danger-based category included two stressor types: Moral Challenges and Witnessing, and the danger-based category included one type: Personal Threat. Thus, three stressor types were explored in relation to self-reported personal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 62 publications
2
18
0
Order By: Relevance
“…More positively, some veterans across all three groups described experiences of posttraumatic growth, including a greater appreciation for life and improved connections with loved ones (Tedeschi & Calhoun, 2004). This experience of psychological growth is in line with previous research in morally injured Norwegian military personnel (Nordstrand et al, 2019). Veterans exposed to morally injurious or 'mixed' events also described a growth in their spirituality or faith following the event; however, this was not consistently observed, and PMIE exposed veterans also described a loss of spiritual beliefs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…More positively, some veterans across all three groups described experiences of posttraumatic growth, including a greater appreciation for life and improved connections with loved ones (Tedeschi & Calhoun, 2004). This experience of psychological growth is in line with previous research in morally injured Norwegian military personnel (Nordstrand et al, 2019). Veterans exposed to morally injurious or 'mixed' events also described a growth in their spirituality or faith following the event; however, this was not consistently observed, and PMIE exposed veterans also described a loss of spiritual beliefs.…”
Section: Discussionsupporting
confidence: 87%
“…Bryan et al, 2014;Jones, 2018;Williamson et al, 2019). The present study illustrates that moral injury can be experienced by veterans following events that were both ethically challenging and life-threatening or otherwise consistent with PTSD criterion A in DSM-5 (Nordstrand et al, 2019). This is notable as the majority of the moral injury literature thus far has not made this distinction; for example, one of the most commonly cited definitions of moral injury (Litz et al, 2009) does not include a reference to the fact that the PMIE may simultaneously be threatening.…”
Section: Discussionmentioning
confidence: 77%
“…However, in many traumatic situations, peritraumatic fear may not be present, and a physical threat may not be the most stressful part of the incident [33,34]. Accordingly, recent studies have distinguished between danger-based and non-danger-based stressors [35]. In the context of the current study, this may help explain why perceptions of inadequacy and even shame, also committing errors, may lead to increased posttraumatic stress reactions.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, studies have demonstrated strong correlations between morally challenging traumas and socially inhibitory feelings such as guilt and shame (Ramage et al, 2016;Jordan et al, 2017;Nordstrand et al, 2019), thus increasing reticence to talk about such experiences (Pietrzak et al, 2009;Gray et al, 2012). Accordingly, it may be important to not only be aware of the potentially morally challenging stressors HCWs face but also help lower barriers toward disclosing such stressors to significant others.…”
Section: Social Support and Personal Barriers To Disclosementioning
confidence: 99%